News Discourse in Translation: Topical Structure and News Content in the Analytical News Article - Károly, Krisztina (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2012)
Topical structure in news translation has received relatively little attention despite its stated significance in discourse content and in producing functionally adequate translations. Journalists write news stories with a given structure, order, viewpoint and values, which are “transferred” in translation and affect the way topics are organized. This study explores how shifts in topical development in translation influence rhetorical structure and ultimately news content. Using Lautamatti’s Topical Structure Analysis and Bell’s Event Structure Model, the paper describes the translation strategies applied in (re)producing the source text’s topical and event structures in the target language in a corpus of Hungarian–English news texts (the summary sections of analytical news articles). Results show that while translators generally preserve the sources’ structure in translation, in some cases (e.g. sequential topic progression) significant changes occur, altering the status of some information as well as the event structure, thus producing modified news contents. The paper also examines whether the claim that news translation is influenced by norms similar to those regulating news production more generally applies to this news genre, too. Findings suggest that due to the stereotypical features of this genre, the data only partially support this claim.